Efektivitas Dan Kesenjangan Penelitian tentang Konten Pembelajaran Secara Personal di Perguruan Tinggi: Sebuah Tinjauan Literatur Kritis - Sitompul, Nurmida Catherine; Suhari; Rusmawati, Retno Danu; Fitriatien, Sri Rahmawati; Degeng, I Nyoman Sudana; Sonia, Putri Nur Aziza; Pangestika, Erika Dea; Fauziah, Laela (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
Personalized teaching materials are an innovation in answering the diversity of student characteristics in higher education. However, its implementation still faces challenges. This study aims to analyse the trends and identify research gaps of personalized teaching materials usages. The method used is a critical literature review of articles from internationally reputable databases. The results of the study show two main findings: (1) there is a transformation in the use of personalized teaching materials in three phases such as: technical and standardization phase; the dynamic pedagogical and adaptive integration phase, and the artificial intelligence and holistic welfare phase; (2) There are four main research gaps such as: inconsistencies in measurement methodology, obstacles to contextual implementation, conceptual ambiguity of personal needs, and limited lecturer readiness. The most valuable finding from  review that the use of PTM where the implementation no longer lies in the "what" is learned but in the "how" the system is intelligently able to empathize with the cognitive and emotional state of learners to create a truly meaningful instructional experience. These are  theoretical contribution in clarifying the evolution of the concept of PTM as well as practical contributions to the development of adaptive learning designs in higher education.